2020
DOI: 10.5194/hess-24-1891-2020
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the environmental response to water harvesting structures: a field study in Tanzania

Abstract: Sand dams, a popular water harvesting structure employed by rural communities, capture and store water for use during the dry season in arid and semi-arid regions. Most sand dam research has been performed on the "ideal" sand dam, despite approximately 50 % of sand dams not functioning as intended. This research involves a 1-year long, in-depth field study of three sand dams in Tanzania, one of which is essentially non-functioning. The study investigated a sand dam's impact on macroinvertebrate habitat, vegeta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(47 citation statements)
references
References 40 publications
0
47
0
Order By: Relevance
“…While evapotranspiration was not identified as a sensitive factor by either Borst and de Haas (2006) or Quinn et al (2018b), Eisma and Merwade (2020) found that a functioning sand dam loses up to 88% of its stored water via evapotranspiration.…”
Section: Water Balancementioning
confidence: 98%
See 4 more Smart Citations
“…While evapotranspiration was not identified as a sensitive factor by either Borst and de Haas (2006) or Quinn et al (2018b), Eisma and Merwade (2020) found that a functioning sand dam loses up to 88% of its stored water via evapotranspiration.…”
Section: Water Balancementioning
confidence: 98%
“…Calculating the water balance for a sand dam requires collection of various inflow and outflow measurements during an extended field study. As a result, only three studies have collected the necessary data (see Table 1) (Borst and de Haas, 2006;Quinn et al, 2019;Eisma and Merwade, 2020). Of the three water balances, only Quinn et al (2019) and Eisma and Merwade (2020) provide an analysis of intra-seasonal sand dam water storage fluxes.…”
Section: Water Balancementioning
confidence: 99%
See 3 more Smart Citations